Study of the European otter's (Lutra lutra) habitat in the Auvergne region (France) : relationships between diet and essential compounds and toxic elements dynamics - Lemarchand, Charles (HAL CCSD, 2007)
The habitat and diet of the otter (Lutra lutra) were studied in the Auvergne region, in relation to the dynamics of essential fatty acids and toxic elements. The movement of natural recolonization of the species leads to frequent aquatic environments degraded and not degraded. Diet dominated by fish, is more diversified in its last. The prey of aquatic origin are a major source of essential fatty acids in tissues of otters, and the ratio DHA / LA is a tool for assessing the origin of terrestrial and aquatic prey. Organochlorine pesticides, PCBs, trace elements and anticoagulants were detected in spraints, tissues, and the main prey of the otter. The concentrations of these elements in tissues, increase along a gradient downstream upstream, within the watershed, due to the transfer of toxic compounds from prey to predator L'habitat et le régime alimentaire de la loutre d'Europe (Lutra lutra) ont été etudiés en région Auvergne, en relation avec la dynamique d'acides gras essentiels et d'éléments toxiques. Le mouvement de recolonisation naturelle de l'espèce l'amène à fréquenter des milieux aquatiques dégradés et non dégradés. Le régime alimentaire, dominé par les poissons, est plus diversifié dans ses derniers. Les proies d'origine aquatique constituent une source majeure d'acides gras essentiels dans les tissus de la loutre, et le rapport DHA/LA constitue un outil d'évaluation de l'origine terrestre ou aquatique des proies. Des pesticides organochlorés, des PCBs ,des éléments traces et des anticoagulants ont été détectés dans les épreintes, les tissus, et les proies principales de la loutre. Les concentrations de ces éléments, dans les tissus, augmentent selon un gradient amont aval, au sein des bassins hydrographiques, en raison du transfert des composés toxiques des proies vers le prédateur